Exposure of Intestinal Epithelial Cells to Short- and Long-Chain Fructo-Oligosaccharides and CpG Oligodeoxynucleotides Enhances Peanut-Specific T Helper 1 Polarization - Hayen, Simone M.; Otten, Henny G.; Overbeek, Saskia A.; Knulst, André C.; Garssen, Johan; Willemsen, Linette E. M. (Frontiers in Immunology, 2018)
Background: Non-digestible oligosaccharides promote colonization of beneficial gut bacteria and have direct immunomodulatory effects. Apical exposure of intestinal epithelial cells (IECs) to short-chain galacto-oligosaccharides and long-chain fructo-oligosaccharides (scGOS/lcFOS) in a transwell co-culture model enhanced the CpG-induced (TLR-9 ligand) Th1-phenotype and regulatory IL-10 response of underlying peripheral mononuclear cells (PBMCs) of healthy donors. scGOS is derived from lactose and may pose risks in severe cow’s milk allergic patients, and scFOS/lcFOS may be an alternative. The goal of this study was to determine the immunomodulatory effects of scGOS/lcFOS and scFOS/lcFOS in an allergen-specific transwell co-culture model using PBMCs from peanut-allergic patients. Methods: IECs cultured on transwell filters were apically exposed to CpG, either or not in combination with oligosaccharides. These IECs were co-cultured with basolateral PBMCs of peanut-allergic patients that were either activated with aCD3/28 or peanut-extract. Basolateral cytokine production and T-cell polarization were measured and the contribution of galectin-9 and the Dectin-1 receptor in immune modulation were assessed. Results: IECs exposed to CpG increased IFN-γ, IL-10 and galectin-9 production by aCD3/28-stimulated PBMCs, whereas IL-13 decreased. Both scGOS/lcFOS and scFOS/lcFOS further enhanced IFN-γ and IL-10, while suppressing IL-13 and TNF-α. In the peanut-specific model, only scFOS/lcFOS further increased IFN-γ and IL-10 production, coinciding with enhanced Th1-frequency. Expression of CRTH2 reduced after CpG exposure, and was further reduced by scFOS/lcFOS. Galectin-9 inhibitor TIM-3-Fc abrogated the additional effect of scFOS/lcFOS on peanut-specific IFN-γ production, while neutralization of the Dectin-1 receptor was not effective. Conclusion: Epithelial exposure to scFOS/lcFOS enhanced the CpG induced Th1 and regulatory IL-10 response in a peanut-specific co-culture model. These effects suggest scFOS/lcFOS as candidate for dietary adjunct in allergen-specific immunotherapy.